THE TRANSLATION OF CULTURE-SPECIFIC CONCEPTS IN DESCRIPTIVE TEXT OF MUSEUM WAYANG DAN ARTEFAK PURBALINGGA - Purwaningsih, Dyah Raina; Yulianita, Nadia Gitya; Prasetyoningsih, Tri Wahyu Setiawan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
The article discusses translation techniques applied in the translation of culture-specific concepts in the description text  of Museum Wayang dan Artefak Purbalingga. Culture-specific concept is one of the common types of non-equivalence at word level resulted from the absence of cultural concepts in the target language. To cope with this problem, a translator is provided with translation techniques proposed by many translation scholars. This research applied the theory of translation techniques proposed by Molina and Albir. Based on the analysis, the most frequently-used technique is borrowing technique. The technique is relatively common to apply in translating culturally-bound terms that do not have one-to-one correspondence. The most common non-equivalence problem at word level to find is problem of culture-specific concepts. It is because the text describes the puppets displayed there, and to be more specific, puppets are parts of Indonesian culture, a precious cultural heritage.  Therefore, many culturally-bound words or terms are kept original.